Optimization Of Plastic Injection Manufacturing Process To Minimize Defects In Motorcycle Components AT PT XYZ - Naufal Khairum; Nurman Nurhakim; M Sahrul Hidayat (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
PT XYZ is one of the largest two-wheeled automotive manufacturers that utilizes the plastic injection molding process to produce motorcycle body components, where the visual quality and dimensional stability of polymer-based exterior parts are critical to the final product aesthetics. The use of recycled material (regrind) from rejected products and runner systems via a crusher process often triggers melt viscosity fluctuations inside the heating barrel. This variation consequently induces physical defects such as sink marks, flash, and short shots on the plastic injection molding machines. This study aims to optimize the molding process parameters to minimize the defect rate of exterior body components using Response Surface Methodology (RSM) with a Central Composite Design (CCD) approach. Actual full-scale experiments were conducted on a 1300-Ton KraussMaffei two-platen machine equipped with Magnetic Clamping System technology, utilizing a material formulation blend of 75% Natural ABS, 5% Black Masterbatch, and 20% regrind. The optimized parameters include injection pressure, melt temperature, holding pressure, and cooling time. The response surface analysis revealed that the most optimal operating parameter combination was achieved at an injection pressure of 168 MPa, a melt temperature of 248°C, a holding pressure of 112 MPa, and a cooling time of 24 seconds. The implementation of these optimal settings on the actual production floor successfully reduced the total component defect rate significantly from an initial 4.20% down to 0.85%.